Student-produced concept cartoon photovoice effects on learners' grit and concept understanding in science - Gamol, Pearl Joy F.
The study aimed to investigate the effects of the Student-Produced Concept Cartoon Photovoice Approach (SPCCPVA) on learners’ grit and concept understanding in science. SPCCPVA integrates concept cartoons and Photovoice into teaching science concepts, principles, and laws. One of the objectives of the study was to describe the nature of Student-Produced Concept Cartoons Photovoice (SPCCPV). The study also aimed to determine whether students exposed to SPCCPVA achieved higher mean posttest scores in Grit-S and Concept Understanding Test in Science (CUTS) than those exposed to the Conventional Teaching Approach (CTA). Additionally, it explored the relationship between grit and concept understanding.